2021
DOI: 10.4314/ahs.v21i4.46
|View full text |Cite
|
Sign up to set email alerts
|

Exclusive breastfeeding practice and its associated factors among children aged 6-23 months in Woldia Town, Northwest Ethiopia

Abstract: Background: Inappropriate practice of exclusive breastfeeding (EBF) is still a major problem worldwide.Objective: To identify exclusive breastfeeding practice and its associated factors among children aged 6-23 months in Woldia Town.Methods: A Community based cross-sectional study was carried out.Interviewer-administered questionnaire was utilized to collect the data. The questionnaire was adapted from the 2016 Ethiopia Demographic and Health Survey. Hosmer-Lemeshowmodel was fitted at a P-value of 0.91. Finall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 26 publications
1
2
0
3
Order By: Relevance
“…Mothers who assumed the role of household head were found to be less likely to engage in EBF compared to those whose household head was male. This finding is supported with the previous studies done in Ethiopia, for instance, Woldia town [ 31 ], and Hossana town [ 33 ]. This could be attributed to the impact of the increased workload on mothers, resulting in reduced time available for feeding the child.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Mothers who assumed the role of household head were found to be less likely to engage in EBF compared to those whose household head was male. This finding is supported with the previous studies done in Ethiopia, for instance, Woldia town [ 31 ], and Hossana town [ 33 ]. This could be attributed to the impact of the increased workload on mothers, resulting in reduced time available for feeding the child.…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies conducted in Ethiopia have identified that early initiation of breastfeeding and exclusive breastfeeding practices are challenged by various maternal, child and health service-related predictors. These factors include maternal age [ 17 19 ], child age [ 20 23 ], marital status [ 20 , 23 , 24 ], employment status [ 16 , 17 , 19 , 21 , 25 , 26 ], religion [ 27 ], educational status of mothers [ 20 , 23 , 28 , 29 ], household wealth index [ 18 , 20 , 22 , 23 , 30 ], ownership of a radio or television [ 28 ], sex of household head [ 31 – 33 ], Parity [ 34 36 ], sex of child [ 28 , 30 , 37 , 38 ], number of family members [ 16 ], residence [ 17 , 23 , 39 , 40 ], receive infant feeding counselling [ 17 , 21 , 22 , 25 ], mothers who had no access to health facility [ 24 ], practicing prelacteal feeding [ 19 ], institutional delivery [ 16 , 18 , 19 , 21 , 23 , 25 , 29 …”
Section: Introductionmentioning
confidence: 99%
“…Hari-hari pertama setelah persalinan kadar estrogen dan progesteron mengalami penurunan secara drastis yang mengakibatkan hormon prolaktin lebih tinggi sehingga mulai terjadi pengeluaran ASI (Nurakilah et al, 2019) (Yimer et al, 2021).…”
Section: Pembahasanunclassified
“…This may be an indication of the absence of childcare facilities, lack of flexibility in working hours, non-initiation of mother-friendly policies in the workplace that support breastfeeding. In addition, working mothers may have enough income to afford formula milk (Yimer et al, 2021). 4.…”
Section: The Effect Of Employment On Exclusive Breastfeedingmentioning
confidence: 99%